The gene expression and immunohistochemical time‐course of diphenylcyclopropenone‐induced contact allergy in healthy humans following repeated epicutaneous challenges. Issue 10 (9th July 2017) - Mose, Kristian F.; Burton, Mark; Thomassen, Mads; Andersen, Flemming; Kruse, Torben A.; Tan, Qihua; Skov, Lone; Røpke, Mads A.; Litman, Thomas; Clemmensen, Ole; Kristensen, Bjarne W.; Friedmann, Peter S.; et al.
Abstract: The gene expression time‐course of repeated challenge of contact allergy (CA) remains largely unknown. Therefore, using diphenylcyclopropenone (DPCP) as model allergen in healthy humans we set out to examine: (i) the monotonous and complex gene expression time‐course trajectories following repeated DPCP challenges to find the predominant gene expression pattern, (ii) the time‐course of cell infiltration following repeated DPCP challenges and (iii) the transcriptome of a repeated CA exposure model. We obtained punch biopsies from control and DPCP‐exposed skin from ten DPCP sensitized individuals at 5‐6 monthly elicitation challenges. Biopsies were used for microarray gene expression profiling, histopathology and immunohistochemical staining. Validation of microarray data by qRT‐PCR was performed on 15 selected genes. Early gene expression time points were also validated in an independent data set. An increasing and decreasing trend in gene expression followed by a plateau was predominantly observed during repeated DPCP challenges. Immune responses reached a plateau after two challenges histopathologically, immunohistochemically and in the time‐course gene expression analysis. Transcriptional responses over time revealed a Th1/Th17 polarization as three upstream regulators (IFN‐γ, IL‐1 and IL‐17) activated most of the top upregulated genes. Of the latter genes, 9 of 10 were the same throughout the time course. Excellent correlations between array and PCR data were observed. The transcriptional responses to DPCP over time followed a monotonous pattern. This response pattern confirms and supports the newly reported clinical time‐course observations in de novo‐sensitized individuals showing a plateau response, and thus, there is concordance between clinical response, histopathology, immunohistochemistry and microarray gene expression in volunteers de novo‐sensitized to DPCP.